Recent advances and future prospects in topical creams from medicinal plants to expedite wound healing: a review - Iliyasu Datti Gwarzo; Siti Pauliena Mohd Bohari; Roswanira Abdul Wahab; Arifullah Zia (Biotechnology & Biotechnological Equipment, 2022)
AbstractWound healing is a complex process driven by a series of stages that require a suitable wound closure environment, attributable to many factors. However, several factors contribute to delay in healing processes, including infection and the presence of certain diseases. Under unfortunate circumstances, an inadequate wound healing process could lead to amputation. Gauze is the traditional dressing to cover up wounds but tends to dry the wound bed. Therefore, a moist dressing may prove helpful in providing a suitable environment, preventing skin dryness, and enhancing angiogenesis of the wound area. The application of topical cream could expedite wound healing better than a moist dressing, as the former facilitates the repair process by maintaining the hydration levels of the affected skin. The issues mentioned above are discussed in detail in this review paper, focusing on recent advances, advantages and drawbacks of topical creams for wound treatment. In addition, the article includes suggestions to improve topical cream formulations for effective delivery of the needed therapeutic agents to assist in wound repair. Crucially, topical creams could play a key role in personal wound care and facilitate regenerative medicine. Novel strategies for speedy wound healing are in demand to alleviate the healthcare financial burden.